A Physical Activity Intervention Feasibility Study for Kidney Inpatients: A Basic Research Protocol. (January 2021) - Wytsma-Fisher, Kathryn; Mustata, Stefan; Cowan, Theresa; Ester, Manuel; Culos-Reed, S. Nicole
Background: Low physical activity levels and poor physical functioning are strongly associated with poor clinical outcomes and mortality in adult kidney failure patients, regardless of treatment modality. Compared with the general population, individuals with chronic kidney disease are physically inactive, have reduced physical abilities and difficulties performing routine daily tasks, lower health-related quality of life, and higher cardiovascular morbidity and mortality. In addition, frail kidney failure patients have higher hospitalization and mortality rates as compared with other kidney failure patients. Evidence suggests that assessment and recommendations for physical activity should be part of standard care for kidney failure patients. Structured exercise can improve physical function and quality of life in frail older adults and may be used specifically for management of frailty in kidney failure. However, research is needed to determine best practices for implementation of physical function measurements and physical activity promotion in standard kidney failure care. Objective: The proposed Move More study will assess the feasibility of a physical activity intervention offered to the kidney failure inpatients in Calgary, Alberta. Specifically, this study is designed to examine the effects of an early physical activity/mobility intervention led by a kinesiologist, and supported by the clinical care team including physiotherapists (PT) and nurse clinicians. Methods: The Move More study is a single-arm pilot intervention examining feasibility and optimal improvement in real-world conditions. Kidney failure inpatients at the Foothills Medical Centre will be recruited to participate. Patients will receive an individualized in-hospital physical activity/mobility intervention. Frailty and physical function will be assessed at baseline and postintervention prior to hospital discharge. The goal is to recruit 24 to 36 patients. Conclusions: Evidence needed to support the inclusion of mobility and physical activity as part of standard care will be gathered, with knowledge gained used to help direct future physical activity programming for kidney failure inpatients.